2011
DOI: 10.1007/s10548-011-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Use It or Lose It? Lessons Learned from the Developing Brains of Children Who are Deaf and Use Cochlear Implants to Hear

Abstract: In the present paper, we review what is currently known about the effects of deafness on the developing human auditory system and ask: Without use, does the immature auditory system lose the ability to normally function and mature? Any change to the structure or function of the auditory pathways resulting from a lack of activity will have important implications for future use through an auditory prosthesis such as a cochlear implant. Data to date show that deafness in children arrests and disrupts normal audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 56 publications
(87 reference statements)
0
52
2
5
Order By: Relevance
“…Although expected cortical electrophysiologic responses were measured from the first implanted ear, responses from the second, laterimplanted ear remained abnormal. [114][115][116][117] The developing auditory brainstem, the first point of binaural integration in the ascending pathways, is already affected. Brainstem responses rapidly change over the first year of unilateral CI use in children with early-onset deafness.…”
Section: Evidence For An Aural Preference Syndromementioning
confidence: 99%
“…Although expected cortical electrophysiologic responses were measured from the first implanted ear, responses from the second, laterimplanted ear remained abnormal. [114][115][116][117] The developing auditory brainstem, the first point of binaural integration in the ascending pathways, is already affected. Brainstem responses rapidly change over the first year of unilateral CI use in children with early-onset deafness.…”
Section: Evidence For An Aural Preference Syndromementioning
confidence: 99%
“…It is more likely that this can be explained by aberrant development of the auditory brainstem and, most of all, the auditory cortex. Studies in children using cochlear implants (Gordon et al, 2011) and animal models (Butler & Lomber, 2013) have shown that the subcortical nuclei of the auditory brainstem require auditory input for further maturation; a sophisticated tonotopy, for instance, does not develop (Butler & Lomber, 2013). Synaptic activity in the primary auditory cortex will deviate substantially from normal including less activation of the deeper cortical layers (Kral, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although CIs can stimulate developmental plasticity in the auditory brainstem even after many years of deafness in childhood, changes in the auditory cortex are limited. This might also be caused - at least in part - by the degree of reorganization which occurred during the period of deafness [45]. In accordance, a recent study using positron emission tomography showed differences in cerebral functions at several points after CI implantation between adults with pre- and postlingual deafness.…”
Section: Discussionmentioning
confidence: 76%